PEMANFAATAN E-JUMANTIK SEBAGAI UPAYA MENDUKUNG SDGS DALAM PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN KUDU KECAMATAN GENUK - Mulyawati, Isti; Purnamasari, Dewi; Nayazik, Akhmad (LPPM Universitas Bina Bangsa, 2024)
Dengue Hemorrhagic Fever (DHF) cases in Kudu Village, Genuk District, Semarang City, have increased significantly in recent years. Prevention efforts through the one house one Jumantik (mosquito larvae monitoring officer) program are considered to still have obstacles, especially in terms of data collection and processing which is carried out manually. This community service aims to develop and implement an Android-based E-Jumantik application as an innovative solution in supporting the Jumantik program and supporting the achievement of the Sustainable Development Goals (SDGs), especially in the aspect of sustainable health. The methods used in this service include socialization to the community, training on the use of the application for Jumantik cadres, implementation of the application in the field, as well as mentoring and evaluation. The results of the service show that the E-Jumantik application is able to increase efficiency and accuracy in collecting mosquito larvae monitoring data. In addition, this application facilitates the reporting and monitoring process, thus enabling early detection of the potential spread of DHF. From the implementation of this program, there has been an increase in the knowledge and skills of Jumantik cadres in using technology, as well as an increase in public awareness regarding DHF prevention. The E-Jumantik application provides a significant contribution in optimizing the management of mosquito larvae monitoring and is expected to be adopted in other regions as a preventive measure to reduce the number of dengue fever cases